Renewable Energy in the Countryside. - Prag, Peter (Taylor and Francis, 2012)
Climate change has become a major international issue and the British Government is committed to meeting ambitious targets for reducing greenhouse gas emissions within the present decade and beyond. Much of this will rely on an increasing use of renewable energy. Within current technology this will depend almost exclusively upon the use of rural land, whether for wind turbines, for growing biomass and biofuels or for the production of biogas. Renewable energy is therefore of immediate interest to farmers and landowners and to their advisers, such as surveyors, lawyers, accountants and bankers.